Ploidy determination of bougainvillea varieties using flow cytometry - YADAV, PRIYA; SINDHU, S.S.; NAMITA; GOPALA KRISHNAN S.; M.R. DHIMAN; BABITA SINGH; MANISH SRIVASTAVA; AMOL SOLANKE (Journal of Ornamental Horticulture, 2024)
Bougainvillea is one of the important ornamental crop with numerous use in floriculture and landscaping. To develop new superior varieties to curb the increasing demanding population there is need to know the ploidy status of currently available varieties of bougainvillea. Flow cytometry is a recent technology that is used to analyse the physical and chemical characteristics of particles in a fluid as it passes through at least one laser, it's a fast and accurate method widely used in ploidy estimation. Most of the elemental varieties are found to be diploid and very few polyploids are present in the study done.